ANALISIS PERBANDINGAN EFISIENSI TEMPAT PELELANGAN IKAN (TPI) TASIKAGUNG, KARANGANYAR, DAN SARANG DI KABUPATEN REMBANG - Rahayu, Listyo; Rosyid, Abdul; Boesono, Herry (Journal of Fisheries Resources Utilization Management and Technology, 2012)
The biggest source of District pure income in Rembang Regency was captured from fishery production value that landed in auction place, TPI has an important role in fishing port and should be managed as well to reach the optimum function. But, not all the facilites and infrastructure are well available and optimum, that cause TPI efficiency. The purpose of this study was to identify the facilites and infrastructure, analyze the efficiency, and efficiency comparison of Tasikagung, Karanganyar, and Sarang fish auctin place in Rembang Regency. The reseach method in this reseach was descriptive method, while the sampling method was purposive sampling. Data analysis methods are Data Envelopment Analysis (DEA) Banxia Fontier Analysis. The result show that the identificatin the existing the facilites and infrastructure of the third in Rembang Regency was the auction floor is perforated, sanitation facilities dan garbages were disfunction, and nothing fish storage. The result of anlilysis of TPI Tasikagung and Sarang were got scor 100 %, while TPI Karanganyar 97,93%. To achieve efficient so needed to be reduction or increase input and output according to the potential value improvement.